Psychiatric genetics: the case of single gene disorders. - Steyaert J; Fryns J (European Child & Adolescent Psychiatry, 2002)
Quantitative and molecular genetics have made important developments in the last three decades. There is increasing evidence of the role of heredity in the field of neuropsychiatric disorders in children. So far, only a few pathways between genes and behaviour have been unravelled.Quantitative genetics puts polygenic inheritance models forward. Molecular genetic research based on these models seems promising, but until now has provided only a limited explanation for the variance in the studied neuropsychiatric disorders. In these models the complexity of the expression of a single gene grows exponentially with the number of genes involved. Consequently, research on the gene-phenotype relationships and phenotypical variability in such models is extremely complex.The candidate gene approach, in which the gene-phenotype pathway of a single gene is studied, is more manageable, and in our opinion essential in understanding multiple gene models. We discuss recent findings in the field and their relevance for neuropsychiatric phenotypes. Single gene defects will only explain a part of the range of neuropsychiatric disorders in children, but the evidence that this approach can generate may help to clarify neuropsychiatric phenotypes. The discovery of single gene disorders in subgroups of subjects with a neuropsychiatric phenotype may result in new perspectives for their treatment.